Awareness and perception of epidural labor analgesia among pregnant women visiting antenatal clinic in National Referral Hospital - Tshomo, Tandin; Tenzin, Karma; Tshering, Jamphel (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To assess the awareness and perception of labour epidural analgesia among pregnant women visiting the antenatal clinic. Methods: This was an observational cross-sectional study. Study participants included pregnant women visiting the antenatal clinic during 2nd and 3 rd trimester conducted from 21 st September 2018 till 20 th September 2019. Data were collected by using an interviewer-administered questionnaire. Ethics approval was granted by the research Ethics Board of health, Bhutan. Results: Total 450 parturients participated in this study; 61.4% of the participants knew that labour epidural services were available and 37.5% got information through media. A total of 57.3% of respondents had severe fear about labour pain; 62.4% had severe fear about delivery complication; 85.2% thought that epidural labour analgesia was a good method of pain relief; and 67% were willing to accept it for their current pregnancy. However, 86.6% would recommend epidural labour analgesia as an option of pain relief to other pregnant women. Conclusion: Awareness about the availability of labour epidural analgesia services needs to be improved, as a majority of the parturient was keen to avail epidural analgesia after the information about its availability was provided.